Experiences of Muslim patients living with peritoneal dialysis: A qualitative study in Southern Thailand - Seephom, Sunisa; Balthip, Karnsunaphat; Jittanoon, Piyanuch (Belitung Nursing Journal, 2024)
Background: Living with peritoneal dialysis affects the patient’s life. The experiences of peritoneal dialysis patients, especially Muslim patients, are incomprehensible. There is a need to explore this area further to foster nursing practice improvement through enhanced understanding. Objective: The purpose of this study was to understand the experiences of Muslim patients who are undergoing peritoneal dialysis. Methods: A qualitative descriptive design was employed to gain a deeper understanding of the experiences of Muslim patients undergoing peritoneal dialysis in a peritoneal dialysis unit in Southern Thailand. Participants were initially recruited through purposive sampling and then selected based on the inclusion criteria. Data saturation was reached from October 2019 to January 2020. Ten Muslim patients who had been receiving peritoneal dialysis for a minimum of one month participated in personalized, in-depth, face-to-face interviews, which were supplemented by field notes. Inductive content analysis was performed using open coding, categories, and abstractions. Results: The experiences of Muslim patients undergoing peritoneal dialysis were grouped into two main categories: 1) Overwhelmed by change and 2) Learned to survive. Conclusion: Peritoneal dialysis has a significant impact on Muslim patients, especially during the first months of treatment. Recognizing religious teachings and strengthening religious commitment through participation in religious practices are central to living on peritoneal dialysis. The findings offer a more profound insight into the experiences of Muslim patients receiving peritoneal dialysis. These results can be foundational knowledge for establishing and improving culturally appropriate nursing practices for Muslim patients.